Making Sense of Apocalyptic Pandemic through Literary Work - N Heriyati (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The paper aims to investigate the effect of literary works on mental health. Various studies shows that literature can contribute to cope and understand mental health. In facing covid 19, people tried to comprehend the situation by searching the related narration on Spanish flu and other pandemic. Pandemic is like absurd situation that abruptly change the world in terms of economic, employment, education, etc. The study uses textual analysis method that obtain data through observation of various primary and secondary textual data. Drawing on the theory of cognitive affective narrative, the study shows that casualty may be experienced by the body and then affect mental health. Family who lost its member may find it difficult to move on since there is no time to mourn and see the love one for the last time. Literary works has performative and expressive element that help people to understand catastrophic situation and recover form painful experienced for losing the one they loved. It leads to the optimism towards the better future.